2017
DOI: 10.1021/acssuschemeng.7b00021
|View full text |Cite
|
Sign up to set email alerts
|

Lignopolymer Superplasticizers for Low-CO2 Cements

Abstract: Grafting hydrophilic polyacrylamide from a kraft lignin core results in a lignopolymer that effectively plasticizes portland cement paste. Here, the potential of this sustainably sourced lignopolymer is examined for improving the workability of portland cement blended with two natural, finely divided mineral materials (kaolin clay and clinoptilolite zeolite), which can be potentially used in combination with portland cement as a means to reduce the cement clinker content and the concomitant embodied energy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…The Takayanagi model is so close to the experimental values by considering E 0 = 2.5 GPa and E 1 = 1,054 GPa. The modulus values shown by composites are greater than the theoretical values because of higher reinforcement effect of MWCNT [38]. This is more visible in composite with 2 wt% MWCNT.…”
Section: Cole-cole Plotmentioning
confidence: 77%
“…The Takayanagi model is so close to the experimental values by considering E 0 = 2.5 GPa and E 1 = 1,054 GPa. The modulus values shown by composites are greater than the theoretical values because of higher reinforcement effect of MWCNT [38]. This is more visible in composite with 2 wt% MWCNT.…”
Section: Cole-cole Plotmentioning
confidence: 77%
“…Lignin represents, however, a highly abundant natural aromatic feedstock with potentially very interesting applications in a sustainable economy scenario, especially considering the high primary production volumes and the inherently renewable nature of this resource [ 12 ]. Several studies are actually under way for the development of valuable lignin derivatives, such as raw chemicals [ 6 ], polymers [ 13 , 14 , 15 , 16 , 17 , 18 ], high-performance concrete admixtures [ 19 , 20 ], and hydrogels [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that adsorption of PCE onto the surface of cement particles is the precondition for exerting high dispersion efficiency of PCE [ 3 , 20 ]. Carboxyl groups exist in the side chain of PAA, and these active groups can adsorb on the surface of cement particles by means of chemical combination and electrostatic force [ 21 , 22 , 23 ]. In this case, mutual influence on adsorption of PAA and PCE, namely competitive adsorption, may take place.…”
Section: Resultsmentioning
confidence: 99%